2004
DOI: 10.1002/aic.10171
|View full text |Cite
|
Sign up to set email alerts
|

Impinging jet cooling on concave surfaces

Abstract: The numerical modeling of jet impingement cooling onto a semicircular concave surface is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 51 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Among the recent experimental [19] numerically investigated the hydrodynamics of turbulent slot-jet impingement on convex semi-cylindrical surfaces without any heat transfer consideration. Souris and Liakos [20] have done numerical studies on impingement cooling on concave cylindrical surfaces using the standard k-3 model and the Reynolds stress transport model along with the non-equilibrium wall function [21] for both models. They compared their predictions with the experimental data of Choi et al [18] and found a satisfying agreement between the numerical prediction and experimental data using both turbulence models.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recent experimental [19] numerically investigated the hydrodynamics of turbulent slot-jet impingement on convex semi-cylindrical surfaces without any heat transfer consideration. Souris and Liakos [20] have done numerical studies on impingement cooling on concave cylindrical surfaces using the standard k-3 model and the Reynolds stress transport model along with the non-equilibrium wall function [21] for both models. They compared their predictions with the experimental data of Choi et al [18] and found a satisfying agreement between the numerical prediction and experimental data using both turbulence models.…”
Section: Introductionmentioning
confidence: 99%
“…Very few computational studies [15][16][17][18] are reported on jet impingement on concave surface. Kayansayan and Kucuka [15] studied single two dimensional slot jet with symmetry condition.…”
Section: Introductionmentioning
confidence: 99%
“…They presented numerical results for low Reynolds number (up to Re of 600). Jia et al [16] and Souris et al [17] also reported results on slot jet impingement with high Reynolds number of 1780 to 20000 by using different turbulence models. They recommended kmodel to take advantage of simplification and low computational requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical study of slot jet impingement on concave surface was carried out by Souris et al [25] and a higher Nusselt number was noted for H/B = 6.…”
Section: Impingement Cooling Of Curved Surfaces and Turbine Vanesmentioning
confidence: 99%